The Impact of Social Media Towards Students’ English-Speaking Proficiency at English Department of UKI Toraja - Weldy Basongan; Charlie Baka; Nilma Taula’bi’ (Pustaka Digital Indonesia, 2025)
The purpose of to this study is to determine the impact of using social media on students' speaking skills at Universitas Kristen Indonesia Toraja. This research uses qualitative method to analyze the data. The purposive sampling strategy was used to obtain data from 7th semester students of English education. data collection was carried out using interview and observation techniques. The result found that Instagram social media has an effect on speaking fluency, vocabulary improvement, grammar and pronunciation. The impact felt by students experienced a significant increase in fluency, pronunciation and understanding of informal language use. The use of Instagram social media can personalize students' experience to practice speaking, writing, reading and listening skills and even motivate and increase self-confidence. Social media can provide a positive experience for students and teacher by offering engaging, interactive, and supportive content for English language learning, so it is worth considering using social media in education.